Inside Front Cover. (9th August 2018) - Villanueva, V.; Giráldez, B. G.; Toledo, M.; De Haan, G. J.; Cumbo, E.; Gambardella, A.; De Backer, M.; Joeres, L.; Brunnert, M.; Dedeken, P.; Serratosa, J.
Abstract : The cover image, by Vicente Villanueva et al., is based on the Paper Lacosamide monotherapy in clinical practice: A retrospective chart review, DOI:10.1111/ane.12920